Answer:
The point slope form is: (y - 5) = 6/11(x - 7)
Step-by-step explanation:
Giving points are: (7, 5) and (-4, -1)
Find the slope m:
m = (y - y1)/(x - x1)
m = (5 - (-1))/(7 - (-4))
m = 5 + 1/7+ 4
m = 6 / 11 = 6/11
Use the point slope form with point (7, 5) and solve for y:
(y - y1) = (x - x1)
(y - 5) = 6/11(x - 7) - this is the point slope form
y - 5 = 6/11x - 42/11
y = 6/11x - 42/11 + 5
y = 6/11x - 42/11 + 55/11
y = 6/11x + 13/11 - This is the y intercept form
Proof, use (7, 5):
f(x) = 6/11x + 13/11
f(7) = 6/11(7) + 13/11
= 42/11 + 13/11
= 55/11 = 5, giving (7, 5)